Sequential DEXAS: a method for obtaining DNA sequences from genomic DNA and blood in one reaction - Motz, Michael (Oxford University Press, 2003)
Sequential DEXAS (direct exponential amplification and sequencing), a one step amplification and sequencing procedure that allows accurate, inexpensive and rapid DNA sequence determination directly from genomic DNA, is described. This method relies on the simultaneous use of two DNA polymerases that differ both in their ability to incorporate dideoxynucleotides and in the time at which they are activated during the reaction. One enzyme, which incorporates deoxynucleotides and performs amplification of the target DNA sequence, is supplied in an active state whereas the other enzyme, which incorporates dideoxynucleotides and performs the sequencing reaction, is supplied in an inactive state but becomes activated by a temperature step during the thermocycling. Thus, in the initial stage of the reaction, target amplification occurs, while in the second stage the sequencing reaction takes place. We show that Sequential DEXAS yields high quality sequencing results directly from genomic DNA as well as directly from human blood without any prior isolation or purification of DNA.